Determinants of low carbon supply chain in Malaysian manufacturing industry : practices and its relationship on green supply chain operational performance and low carbon performance - Muhammad Shabir, Shaharudin (2019)
Climate change has become one of the most critical sustainability challenges. One of the most evident contributor of climate change is carbon emissions. Therefore, academia and firms are focusing on carbon emissions reduction in both the supply chain and operations as manufacturing and supply chain activities emit high carbon emissions. Nevertheless, the current supply chain model lack of carbon emissions abatement. Thus, this study’s objectives are to develop a theoretical model for low carbon supply chain and to examine the relationship between determinants on low carbon supply chain practices and the practices with low carbon performance. In addition, this study also investigates the mediating effect of green supply chain operational performance. The methodology adopted in this study is of a quantitative method. 700 survey questionnaires were sent out to manufacturing firms registered with Federal of Manufacturers Malaysia and 143 completed questionnaires were collected and analyzed. This study uses IBM SPPS version 24 and SmartPLS version 3.2.8 software to analyze the data. Based on the finding, it shows that low carbon supply chain practices have positive effect on low carbon performance of firms. In addition, the mediating effect of green supply chain operational performance was found to mediate the relationship and improve low carbon supply chain practices of manufacturing firms. It was further found that customer pressure has a coercive nature compared to government regulations. These findings have contributed to the extension of Institutional theory knowledge and the literature of supply chain and operations. The comprehensive low carbon supply chain model has also been proven valid and reliable to help manufacturing firms meet environmental performance and operational performance. The introduction of mediating effect to improve low carbon performance has also contributed to the literature as currently firms are split in decision whether to achieve environmental performance or operational performance. The finding shows that manufacturing firms achieved better results with both performances. Practically, manufacturing firms are recommended to adopt green supply chain operational performance in order to achieve better low carbon performance.